Beneficial Spillover Effects of Antipredation Interventions Support Human–Carnivore Coexistence - Jonathan Salerno; Rekha Warrier; Stewart W. Breck; Neil H. Carter; Joel Berger; Brendan J. Barrett; Justine Robert Lukumay; Joseph Francis Kaduma; Ana Grau; Amy J. Dickman; Kevin R. Crooks (Conservation Letters)
ABSTRACT Reducing human–wildlife conflict is critical for global biodiversity conservation and supporting livelihoods in landscapes where people and wildlife co‐occur. Interventions intended to reduce conflicts and their negative outcomes are diverse and widespread, yet there is often a dearth of empirical evidence regarding effectiveness, particularly at appropriate spatiotemporal scales. We investigate an underappreciated question relevant to large carnivore–livestock systems globally regarding spillover effects of anti‐conflict interventions: Do fortified livestock enclosures modify carnivore predation on livestock for neighbors who lack such interventions? We use ca. 25,000 monthly reports from agropastoralists in an East African landscape critical for large carnivore conservation. Results from Bayesian multilevel statistical models demonstrate robust effects of fortified livestock enclosures in reducing reported predation not only in target households, but also in neighboring households that lack such fortification—a beneficial spillover effect. Results provide empirical evidence for policy and practice regarding tools to reduce large carnivore conflicts while pointing to the important role of complex‐systems processes in determining coexistence outcomes.